2022
DOI: 10.3390/ijerph191811424
|View full text |Cite
|
Sign up to set email alerts
|

Home Office, Health Behavior and Workplace Health Promotion of Employees in the Telecommunications Sector during the Pandemic

Abstract: Our study aims to present the perception and experiences of employees at a large multinational telecommunications company in Hungary working in home offices, as well as their health behavior and the workplace health promotion during the SARS-CoV-2 COVID-19 outbreak. The sample consisted of the full sample of highly skilled employees at a large telecommunication multinational company (N = 46). Throughout the analysis, tests for homogeneity of variance were followed by a MANOVA test to compare the groups’ means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
0
1
Order By: Relevance
“…In Hungary, the majority of those working in home offices did not suffer from deterioration in mental health or relationships with family members. This study also did not support the assumption of home workers being less efficient or less diligent in their daily work (Tánczos et al, 2022). In contrast, a study conducted by Italian researchers found that, among remote workers, family-work conflicts and social isolation had had a negative impact on productivity, while leadership and autonomy alone had had a positive impact on the productivity and work engagement of these workers (Galanti et al, 2021).…”
Section: Introductioncontrasting
confidence: 74%
“…In Hungary, the majority of those working in home offices did not suffer from deterioration in mental health or relationships with family members. This study also did not support the assumption of home workers being less efficient or less diligent in their daily work (Tánczos et al, 2022). In contrast, a study conducted by Italian researchers found that, among remote workers, family-work conflicts and social isolation had had a negative impact on productivity, while leadership and autonomy alone had had a positive impact on the productivity and work engagement of these workers (Galanti et al, 2021).…”
Section: Introductioncontrasting
confidence: 74%